Multiscale modelling approach to determine the specific heat of cementitious materials. Issue 5 (4th May 2019) - Bernard, Fabrice; Fu, Jia; Kamali-Bernard, Siham
Abstract: A hierarchical multi-scale modelling of cement-based materials devoted here to the determination of the mechanical properties and specific heat of this kind of materials is presented in this paper. This multiscale modelling approach is used to study cementitious materials from nanoscale to mesoscale. Despite the tremendous increase in the multi-scale investigations of cement-based materials, the physical origins of their thermal properties at the nanoscale and their upscaling to the macroscopic properties are still little studied. In this paper, through the investigation of the vibrational states of the unit cells of the various phases of the Hardened Cement Paste as well as their energy phonons using the Debye model, we determine the specific heat of these phases. Then the use of the composite spheres assemblage model enables us to calculate this property for a w / c = 0.45 cement paste and the corresponding mortar (870 J/kg/K for the well-hydrated cement paste, and 742 J/kg/K for the mortar) .